KECUKUPAN ASUPAN GIZI REMAJA VEGETARIAN DAN NONVEGETARIAN DI YAYASAN SRI SATHYA SAI BALI TAHUN 2011 - Hildagardis Meliyani; Kadek Tresna Adhi; Ketut Sutiari (Program Studi Sarjana Kesehatan Masyarakat Universitas Udayana Berasosiasi Dengan Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI), 2012)
Vegetarian diet tends to have nutrient de? ciencies in meat sources nutrient. The aim of this studywas to analyze the di? erences in the level of nutrient consumption among teens vegetarian andnon-vegetarian. This study was a cross sectional study.The sampling technique uses a consecutive sampling and consisting of 45 vegetarian and 51 nonvegetarianaged between11-19 years.Food consumption data warecollected by interview usingfoodrecall form.Theresults showedthat the levelof nutrient consumption (energy,protein, calcium, iron, zinc,andvitamin C) in the majority of vegetarianand non-vegetarianare categorised into the low category. There was no signi? cant di? erence in consumption levels of energy, protein, iron, zinc,and vitamin C among vegetarian and nonvegetarian (p>0,05). In addition, there was no signi? cantdi? erence in the level of calcium intake in vegetarians and non-vegetarian (p<0,05).